Investment, as a tool to achieve growth and the eradication of poverty, can be undermined by inappropriate decisions and policies. - Centeno Sarmiento, Jorge Antonio (LACCEI, 2024)
OBJECTIVE. To evaluate the effectiveness of public policy on poverty eradication, based on the historical analysis of investment performance, production, indebtedness, and employment in Honduras. METHOD. A quantitative approach was applied, with applications of mathematical models from databases, expenditures, and income, carrying out a multiple regression model to determine causal relationships between the Gross Domestic Product, investment, debt and poverty, 2012-2022. RESULTS. Even though the amounts of investment and debt utilization grew in percentages higher than the population growth, in percentages of 9.3% and 26.8% respectively, these were not enough, nor quality, to alleviate poverty which grew 5.0% annually and employment which barely showed an annual growth of 1.3%, thus, when performing the correlation of variables it was observed that the levels of poverty show a non-significant negative relationship with the previous variables with an R2 of -0.3049. CONCLUSION. There is no explanatory relationship between the variables, investment, debt and production in the behavior of poverty, since the magnitude of GDP growth of 3.6% and employment growth of 1.3% is insufficient to absorb the labor supply of the new population, As will be seen, the economy is undermined by other indicators inherent to the quality of decision making.